2004
DOI: 10.1089/089771504774129964
|View full text |Cite
|
Sign up to set email alerts
|

The Tale of Phineas Gage, Digitally Remastered

Abstract: The injury of Phineas Gage has fueled research on and fascination with the localization of cerebral functions in the past century and a half. Most physicians and anatomists believed that Gage sustained a largely bilateral injury to the frontal lobes. However, previous studies seem to have overlooked a few less obvious, but essential details. This has led us to reanalyze the injury using three-dimensional reconstruction and quantitative computer-aided techniques and to propose a new biomechanical model, in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 8 publications
0
39
0
2
Order By: Relevance
“…Debate about the exact anatomy of this injury (Damasio et al 1994, Ratiu et al 2004) and the nature of the associated behavioral change continues to this day (Macmillan 2000). The uncertainty around the injury to Gage’s brain and the associated changes in behavior underscore the importance of having precise ways to characterize both the anatomy of brain injuries and the associated behavioral changes.…”
Section: Neurodegenerative Disease: An Opportunity To Study Neural CImentioning
confidence: 99%
“…Debate about the exact anatomy of this injury (Damasio et al 1994, Ratiu et al 2004) and the nature of the associated behavioral change continues to this day (Macmillan 2000). The uncertainty around the injury to Gage’s brain and the associated changes in behavior underscore the importance of having precise ways to characterize both the anatomy of brain injuries and the associated behavioral changes.…”
Section: Neurodegenerative Disease: An Opportunity To Study Neural CImentioning
confidence: 99%
“…Mechanisms and consequences of brain injuries have always been a matter of debate and speculation (Ratiu et al, 2004), and even more so when the injury may not easily be identified by technologies used in clinical practice such as in the case of mild traumatic brain injury (mTBI; Sterr et al, 2006). Since the actual mechanisms of injury are still unclear (Bigler 2008; Ruff, 2005), there is controversy regarding diagnostic criteria for mTBI as well as the relationship between mTBI and some manifestations of posttraumatic stress disorder (PTSD; Andreasen, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One can learn a substantial amount from detailed study of particular individuals (for just a small sampling, see Sacks, 1995; Sacks, 1998; Luria, 1972; Luria, 1976; Van Horn et al, 2012; Ratiu et al, 2004; Eichenbaum, 2013; Worthey et al, 2011), and we believe that we are entering an era of precision medicine in which we can learn from and collect substantial data on informative individual cases. Incorporating insights from a range of scientific and clinical disciplines into the study and treatment of any one person is therefore beginning to emerge as a tractable, and more holistic, approach, and we document here what we believe to be the first integration of deep brain stimulation and whole genome sequencing for precision medicine in the evaluation, treatment and preventive care for one severely mentally ill individual, MA.…”
Section: Discussionmentioning
confidence: 99%